WTO, Compulsory Export Licences and Indian Patent Law - Hafiz Aziz ur Rehman (Nordic Journal of Commercial Law, 2011)
A 2005 publication of UNAIDS, AIDS in Africa: Three Scenarios to 2025, contains several moving stories about HIV/AIDS in Africa, describing how the AIDS epidemic in Africa could evolve over the next 20 years.2 The scenarios set out to answer one central question: over the next 20 years, what factors will drive Africa’s and the world’s responses to the AIDS epidemic, and what kind of future will there be for the next generation? Amongst the various aspects of the problem, access to and uptake of AIDS treatment is discussed and highlighted throughout the document. The publication highlights how crucial Indian pharmaceutical exports are for the treatment of the HIV/AIDS epidemic in Africa.